Emulation of Synaptic Plasticity in WO3‐Based Ion‐Gated Transistors - Ramin Karimi Azari; Luan Pereira Camargo; José Ramón Herrera Garza; Liam Collins; Wan− Yu Tsai; Lariel Chagas da Silva Neres; Patrick Dang; Martin Schwellberger Barbosa; Clara Santato (Advanced Electronic Materials)
Abstract Neuromorphic systems, inspired by the human brain, promise significant advancements in computational efficiency and power consumption by integrating processing and memory functions, thereby addressing the von Neumann bottleneck. This paper explores the synaptic plasticity of a WO3‐based ion‐gated transistor (IGT) in [EMIM][TFSI] and a 0.1 mol L−1 LiTFSI in [EMIM][TFSI] for neuromorphic computing applications. Cyclic voltammetry (CV), transistor characteristics, and atomic force microscopy (AFM) force–distance (FD) profiling analyses reveal that Li+ brings about ion intercalation, together with higher mobility and conductance, and slower response time (τ). WO3 IGTs exhibit spike amplitude‐dependent plasticity (SADP), spike number‐dependent plasticity (SNDP), spike duration‐dependent plasticity (SDDP), frequency‐dependent plasticity (FDP), and paired‐pulse facilitation (PPF), which are all crucial for mimicking biological synaptic functions and understanding how to achieve different types of plasticity in the same IGT. The findings underscore the importance of selecting the appropriate ionic medium to optimize the performance of synaptic transistors, enabling the development of neuromorphic systems capable of adaptive learning and real‐time processing, which are essential for applications in artificial intelligence (AI).